Dopant/Semiconductor/Electret Trilayer Architecture for High‐Performance Organic Field‐Effect Transistors. (17th July 2018) - Wei, Peng; Hu, Yupeng; Zhu, Yuanwei; Jiang, Yihang; Feng, Xiaoshan; Li, Shengtao; Bu, Laju; Yang, Xiaoniu; Lu, Guanghao
Abstract: Polycrystalline organic semiconductors are widely used for thin‐film organic electronics; however, such films are usually featured with charge traps due to various crystalline defects and domain boundaries. Chemical doping and applying external electric field are two representative methods to fill traps and induce free charges to modulate charge transport behaviors. However, for organic field‐effect transistors (OFETs) with high threshold voltages usually induced by charge traps, increasing doping concentration and electric field are frequently inaccessible, energy‐consuming, or even deteriorative to device performance. In this work, using the organic semiconductor 2, 7‐dialkyl[1]benzothieno[3, 2‐b][1]benzothiophene, a combined approach is proposed to synergistically utilize chemical doping and electret induced electric potential for OFET applications, via constructing dopant/semiconductor/electret trilayer architecture. Charges induced by dopant are mainly confined near the dopant/semicondcutor interface, while electrostatic field provided by electret accumulates/depletes charges near semiconductor/electret interface. Although both of doping concentration and charge density in electret are relatively low, which is crucial to warrant high‐performance stable device, the performance of the OFETs is greatly modulated. Moreover, the dopant/semiconductor/electret trilayer structure is optically transparent. Using this method, high‐performance OFETs with field‐effect mobility of ≈6 cm 2 V −1 s −1, subthreshold‐swing of 0.3 V decade −1, on–off ratio exceeding 10 6, and tunable threshold voltages are realized. Abstract : Dopant/semiconductor/electret trilayer architecture is used to modulate organic field‐effect transistor (OFET) performance in a wide range. This trilayer archiecture induces more charges in semiconductors in the on‐state as compared with bilayer structures, and the charges are completely depleted by gate voltage in the off‐state. OFETs with high mobility, sharp shreshold swing, high on–off ratio, and tunable threshold voltages are realized.